2008
DOI: 10.1107/s174430910801381x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and structure determination of the core-binding domain of bacteriophage lambda integrase

Abstract: Bacteriophage lambda integrase catalyzes site-specific DNA recombination. A helical bundle domain in the enzyme, called the core-binding domain (Int(CB)), promotes the catalysis of an intermediate DNA-cleavage reaction that is critical for recombination and is not well folded in solution in the absence of DNA. To gain structural insights into the mechanism behind the accessory role of this domain in catalysis, an attempt was made to crystallize an Int(CB)-DNA complex, but crystals of free Int(CB) were fortuito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A composite omit map contoured at 0.5 sigma is presented in Figure 1B, and illustrates that the chain does appear to be continuous in this region, albeit with very weak electron density. A search for structurally related proteins in the PDB (Table S1) using the DALI algorithm [41] revealed that the most closely related structure to the N-terminal domain of XerA (residues 9 to 90) is the core-binding domain of λ-Int [42]. Superimposition of these domains gives an r.m.s.d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A composite omit map contoured at 0.5 sigma is presented in Figure 1B, and illustrates that the chain does appear to be continuous in this region, albeit with very weak electron density. A search for structurally related proteins in the PDB (Table S1) using the DALI algorithm [41] revealed that the most closely related structure to the N-terminal domain of XerA (residues 9 to 90) is the core-binding domain of λ-Int [42]. Superimposition of these domains gives an r.m.s.d.…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal domain consists of two hairpins, each composed of two anti-parallel helices. These two hairpins are perpendicular to each other in the same cruciform arrangement adopted by the four-helix bundle constituting the core-binding domain of λ Int [42] or the N-terminal domains of XerD [15] and IntIA [12]. Structure comparison of λ Int N-terminal domain in the absence of DNA with the full size λ Int bound to DNA [45], revealed that upon DNA-binding, the N-terminal domain shows only subtle rearrangements, mostly affecting residues involved in DNA contact.…”
Section: Resultsmentioning
confidence: 99%
“…3, the λ Int CTD consists of a catalytic domain that is joined to the central binding (CB) domain by a flexible, interdomain linker, residues I160-R176, that is extremely sensitive to proteolytic degradation (45, 48). The CB and catalytic domains of Int both contribute to recognition of the core site, although the former, whose structure has also been determined (68), confers most of the sequence specificity (69, 70). Only two residues from each domain (K95 and N99 in the CB domain and K235 and R287 in the catalytic domain) directly form hydrogen bonds with DNA bases.…”
Section: Structure Of the Int Ctdmentioning
confidence: 99%
“…A composite omit map contoured at 0.5 sigma is presented in Figure 1B, and illustrates that the chain does appear to be continuous in this region, albeit with very weak electron density. A search for structurally related proteins in the PDB (Table S1) using the DALI algorithm [41] revealed that the most closely related structure to the N-terminal domain of XerA (residues 9 to 90) is the core-binding domain of l-Int [42]. Superimposition of these domains gives an r.m.s.d.…”
Section: Structure Determinationmentioning
confidence: 99%
“…The N-terminal domain consists of two hairpins, each composed of two anti-parallel helices. These two hairpins are perpendicular to each other in the same cruciform arrangement adopted by the four-helix bundle constituting the core-binding domain of l Int [42] or the N-terminal domains of XerD [15] and IntIA [12]. Structure comparison of l Int N-terminal domain in the absence of DNA with the full size l Int bound to DNA [45], revealed that upon DNA-binding, the N-terminal domain shows only subtle rearrangements, mostly affecting residues involved in DNA contact.…”
Section: Architecture Of Apo-xeramentioning
confidence: 99%